The Intensive Margin in Trade - Fernandes, Ana M. (World Bank, Washington, DC, 2018)
Is the variation in bilateral trade flows across countries primarily due to differences in the number of exporting firms (the extensive margin) or in the average size of an exporter (the intensive margin)? And how does this affect the estimation and quantitative implications of the Melitz (2003) trade model? The benchmark Melitz model with Pareto-distributed firm productivity and fixed costs of exporting, predicts that, conditional on the fixed costs of exporting, all variation in exports across trading partners should occur on the extensive margin. This paper subjects this theoretical prediction to a reality check drawing upon the World Bank's Exporter Dynamics Database (EDD) which has firm-level exports from 50 developing countries to all destinations. Around 50 percent of the variation in exports across trading partners is shown to be along the intensive margin, contradicting the benchmark Melitz-Pareto model. The paper finds that moving from a Pareto to a lognormal distribution of firm productivity allows the Melitz model to successfully match the role of the intensive margin evident in the EDD. The paper then studies the implications of our findings for quantitative trade theory. Using likelihood methods and the EDD, a generalized Melitz model with a joint lognormal distribution for firm productivity, fixed costs and demand shifters is estimated, and exact hat algebra is used to quantify the counterfactual effects of a decline in trade costs on trade flows and welfare in the estimated model. Finally, these effects are compared to those that would be predicted by the Melitz-Pareto model, with the Pareto shape parameter chosen to match the average trade elasticity implied by the estimated Melitz-lognormal model. The paper shows that the effects on welfare turn out to be quite close to those in the standard Melitz-Pareto model even though the effects on trade flows remain different.